Mechanoluminescence properties of SrAl2O4: Tb3+ phosphor - Sao, Sanjay Kumar S; Brahme, Nameeta; Bisen, D P; Tiwari, Geetanjali; Tigga, Shalinta; Sahu, Ishwar Prasad; Kurrey, Ugendra (Recent Research in Science and Technology, 2012)
Through the execution of experimental investigation, Mechanoluminescence of SrAl2O4:Tb3+ phosphor was studied which is synthesized by combustion method. In the observation, the peak value of ML depends on the different impact velocity. It was seen that at 55 cm height, the maximum peak of ML is obtained.